Performance Assessment of Physico-Mechanical Properties of Aloji Fireclay Brick - Ajala, Amkpa Job; Badarulzaman, Nur Azam (International Journal of Integrated Engineering, 2016)
This research evaluated the physical and mechanical properties of Aloji fireclay brick’s suitability for production of refractory fireclay brick as furnace linings. At the optimum sintering temperature of 1200 0C, the Aloji fireclay brick had apparent porosity value of 23.62 %, bulk density was 1.76 g/cm3, firing shrinkage value of 8.62 %, water absorption of 7.77 % and CCS was 15.8 MPa. It was observed that as the sintering temperatures were increased the porosity, bulk density, firing shrinkage and the CCS were linearly increased. This then means that the varied sintering temperatures have significant influence on the physical and mechanical properties of the Aloji fireclay brick.